Pictures in Enhancing Students' Vocabulary Mastery of the Eight Grade at MTS Al- Qamariah Popidolon - Desriani Nggolaon; Alya Gempita; Nur Syariatin (English Education Study Program, 2022)
The purpose of this research was to identify the enhancement of students' vocabulary mastery through the use of pictures at MTS Al-Qamariah Popidolon. The research used pre-experimental design. There were two variables in this research, the independent variable and dependent variable. The independent variable was the use of pictures and the dependent variable was the students’ vocabulary mastery. The population of this research was the eight grade at MTS Al- Qamariah Popidolon and the researcher used total sampling technique in selecting the sample. The data was collected by using test which was consist of pretest and posttest which was given to the students. Pretest was given in the first meeting, and then posttest in the last meeting after giving treatment by using pictures in enhancing students’ vocabulary. After calculating the data, the results showed that the t-counted 14.716 was greater than the t-table 2.144. Therefore, the alternative hypothesis was accepted and the null hypothesis was rejected. It can be concluded that there was an enhancement on students’ vocabulary using pictures at MTS Al-Qamariah Popidolon.